Development Of A Realtime IoT Smart Home Monitoring System Using ESP8266, ThingsBoard, And Telegram Bot - Nur Awalia Sekar; Adi Wibowo (International Journal of Health Engineering and Technology, 2026)
The rapid advancement of Internet of Things (IoT) technology has significantly contributed to the development of intelligent automation systems for residential environments. This study aims to design and implement an IoT-based Smart Home system using the NodeMCU ESP8266 microcontroller for realtime monitoring and control applications. The proposed system integrates several hardware components, including the YF-S201 water flow sensor for monitoring water flow rate and total water consumption, the MQ2 gas sensor for gas leakage detection, a 3-channel relay module for household lighting control, and a buzzer alarm as an early warning mechanism. Furthermore, the system is integrated with ThingsBoard Cloud and Telegram Bot to support realtime monitoring, remote control, and automatic notification services through internet communication using the MQTT protocol. This research employed an experimental method with a prototype-based development approach involving system requirement analysis, hardware and software design, system integration, implementation, and performance testing. The system was implemented and tested at a residential environment located in North Lampung Regency, Indonesia. The testing process evaluated the performance of water monitoring, gas detection, notification delivery, and lighting control functionalities. The results demonstrated that the developed Smart Home system successfully performed realtime monitoring of water flow rate, total water usage, gas leakage conditions, and remote lighting control through cloud-based communication. The water flow sensor achieved an average reading of 8.82 liters per minute with cumulative water usage reaching 50 liters during testing. In addition, the MQ2 gas sensor successfully detected dangerous gas conditions and automatically activated the buzzer alarm while simultaneously sending warning notifications through Telegram Bot with a testing success rate of 100%. The relay module also successfully controlled all household lighting devices remotely through the ThingsBoard dashboard with stable MQTT communication and low delay response. Overall, the developed IoT-based Smart Home system demonstrated strong capability in improving household monitoring efficiency, environmental safety, and user convenience through intelligent realtime automation technology.